Комплекс щодо захисту від фішингових атак - Кожушко, Д. Р.; Федюшин, О. І. (ХНУРЕ, 2021)
The given work is dedicated to the best practices of awareness of phishing attacks. Phishing attacks are usually very massive, so they can touch anybody. Basic behavior rules can help people save from most attacks and protect their personal data.
Keywords: фішинг; злочинний контент; конфіденційність комп’ютера; антиспам